Population Dynamics and Survival Strategies of Two Endangered Ungulates in a Low Water-Availability Site of the Maya Forest of Mexico - Rafael Reyna-Hurtado; Jonathan O. Huerta-Rodríguez; Alan Duarte-Morales; Itzel Poot-Sarmiento; Lizzi Valeria Martínez-Martínez; Manuel Alejandro Jiménez-Sánchez (Animals)
White-lipped peccary (Tayassu pecari) and Central American tapir (Tapirus bairdii) are two endangered ungulates that inhabit the Maya Forest in Southern Mexico. These species need water sources almost every day to fill their ecological and physiological needs. How have they survived in a landscape like the Calakmul Biosphere Reserve where the water is very scarce and temporal? We analyzed 10 years of data for both species, collected through the intensive use of camera traps located in 18 ephemeral ponds of the Mexican side of the Maya Forest. These data in combination with occasional data on individual movements of both species collected with radiotelemetry allowed us to describe changes in occupancy, abundance, and movements that show the different strategies these species must cope with during dry periods. The white-lipped peccary population passed through cycles and disappeared from periods of water scarcity, and later, they appeared and stayed close to a few sources of water while the tapir population remained constant and occupied almost all sources of water throughout the years. This contribution increases the ecological knowledge and survival strategies of two endangered tropical ungulates of Mesoamerican Forests that have been disappearing at alarming rates in other forests of the region.